LIM‐homeobox gene 2 promotes tumor growth and metastasis by inducing autocrine and paracrine PDGF‐B signaling. Issue 2 (25th December 2013) - Kuzmanov, Aleksandar; Hopfer, Ulrike; Marti, Patricia; Meyer-Schaller, Nathalie; Yilmaz, Mahmut; Christofori, Gerhard
Abstract : An epithelial‐mesenchymal transition (EMT) is a critical process during embryonic development and the progression of epithelial tumors to metastatic cancers. Gene expression profiling has uncovered the transcription factor LIM homeobox gene 2 (Lhx2) with up‐regulated expression during TGFβ‐induced EMT in normal and cancerous breast epithelial cells. Loss and gain of function experiments in transgenic mouse models of breast cancer and of insulinoma in vivo and in breast cancer cells in vitro indicate that Lhx2 plays a critical role in primary tumor growth and metastasis. Notably, the transgenic expression of Lhx2 during breast carcinogenesis promotes vessel maturation, primary tumor growth, tumor cell intravasation and metastasis by directly inducing the expression of platelet‐derived growth factor (PDGF)‐B in tumor cells and by indirectly increasing the expression of PDGF receptor‐β (PDGFRβ) on tumor cells and pericytes. Pharmacological inhibition of PDGF‐B/PDGFRβ signaling reduces vessel functionality and tumor growth and Lhx2‐induced cell migration and cell invasion. The data indicate a dual role of Lhx2 during EMT and tumor progression: by inducing the expression of PDGF‐B, Lhx2 provokes an autocrine PDGF‐B/PDGFRβ loop required for cell migration, invasion and metastatic dissemination and paracrine PDGF‐B/PDGFRβ signaling to support blood vessel functionality and, thus, primary tumor growth. Highlights: Lhx2 expression is induced during EMT by canonical TGFβ signaling. Lhx2 expression is elevated during both human and mouse carcinogenesis. Lhx2 promotes primary tumor growth by paracrine PDGF‐B/PDGFRβ signaling‐mediated tumor vessel maturation and functionality. Lhx2 promotes metastasis formation via autocrine PDGF‐B/PDGFRβ signaling‐induced tumor cell migration and invasion.